Retrieval cues that trigger reconsolidation of associative fear memory are not necessarily an exact replica of the original learning experience - Soeter, Marieke; Kindt, Merel (Frontiers in Behavioral Neuroscience, 2015)
Disrupting the process of memory reconsolidation may point to a novel therapeutic strategy for the permanent reduction of fear in patients suffering from anxiety disorders. However both in animal and human studies the retrieval cue typically involves a re-exposure to the original fear-conditioned stimulus. A relevant question is whether abstract cues not directly associated with the threat event also trigger reconsolidation, given that anxiety disorders often result from vicarious or unobtrusive learning for which no explicit memory exists. Insofar as the fear memory involves a flexible representation of the original learning experience, we hypothesized that the process of memory reconsolidation may also be triggered by abstract cues. We addressed this hypothesis by using a differential human fear-conditioning procedure in two distinct fear-learning groups. We predicted that if fear learning involves discrimination on basis of perceptual cues within one semantic category (i.e., the perceptual-learning group, n = 15), the subsequent ambiguity of the abstract retrieval cue would not trigger memory reconsolidation. In contrast, if fear learning involves discriminating between two semantic categories (i.e., categorical-learning group, n = 15), an abstract retrieval cue would unequivocally reactivate the fear memory and might subsequently trigger memory reconsolidation. Here we show that memory reconsolidation may indeed be triggered by another cue than the one that was present during the original learning occasion, but this effect depends on the learning history. Evidence for fear memory reconsolidation was inferred from the fear-erasing effect of one pill of propranolol (40 mg) systemically administered upon exposure to the abstract retrieval cue. Our finding that reconsolidation of a specific fear association does not require exposure to the original retrieval cue supports the feasibility of reconsolidation-based interventions for emotional disorders.